Does Tax Avoidance Matter in Sustainaility Reporting-Financial Performance Relationship: Evidence From Indonesia - Pangestu, Nadya Indah; Supriyati, Supriyati (AKRUAL: Jurnal Akuntansi, 2021)
Financial performance is a measure of the success of a company’s operation. Optimum financial performance is said to be achieved when company operation successfully increases company turnover. Sustainability reporting uncovers the financial and non-financial aspects of this company’s operations. This research aims to examine the effect of sustainability reporting on financial performance with tax avoidance as mediating variable. This research was conducted in 58 companies that led sustainability reporting in the 2014-2018 period. Data were analyzed with regression and causal step testing. This research has some results, which among others are: that sustainability reporting has a positive effect on corporate financial performance and that tax avoidance has a negative effect on corporate financial performance. It was also found that tax avoidance is not mediating variable for the effect of sustainability reporting on corporate financial performance.